Handbook of plastics joining a practical guide - Troughton, Michael John (William Andrew ; TWI/The Welding Institute, 2008)
The new edition of this bestselling reference provides fully updated and detailed descriptions of plastics joining processes, plus an extensive compilation of data on joining specific materials. The volume is divided into two main parts: processes and materials. The processing section has 18 chapters, each explaining a different joining technique. The materials section has joining information for 25 generic polymer families. Both sections contain data organized according to the joining methods used for that material.
Keywords: plasty; polymerní materiály; spojování materiálů; svařování; svarové spoje; plastics; polymer materials; joining of materials; welding; welded joints; příručky; elektronické knihy; handbooks, manuals, etc; electronic books